2018
DOI: 10.3390/vetsci5010022
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Extended-Spectrum β-Lactamase Producing Enterobacteriaceae Occurrence in Farms in Reunion, Madagascar and Mayotte Islands, 2016–2017

Abstract: In South Western Indian ocean (IO), Extended-Spectrum β-Lactamase producing Enterobacteriaceae (ESBL-E) are a main public health issue. In livestock, ESBL-E burden was unknown. The aim of this study was estimating the prevalence of ESBL-E on commercial farms in Reunion, Mayotte and Madagascar and genes involved. Secondly, risk factors of ESBL-E occurrence in broiler, beef cattle and pig farms were explored. In 2016–2017, commercial farms were sampled using boot swabs and samples stored at 4 °C before microbiol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
1
21
1
2
Order By: Relevance
“…The AB resistance patterns per enterprise type revealed that the isolates from poultry farms had the highest resistance rates to TET, SXT, CHL and AMC (Figure 2). These results are in agreement with reports from: (i) Ghana, with high resistance frequencies to TET (88.9%), sulphonamide (75.0%), ampicillin (69.4%) and trimethoprim (66.7%) [25]; (ii) Madagascar broil farms with 97.6% to TET [26]; (iii) Chinese carcasses with ampicillin (98.9%), CHL (92.2%), TET (78.9%) [27]; and (iv) Portuguese healthy chickens with TET (70%), ampicillin (63%) and CIP (49%), however, with lower frequencies for SXT (33%), CHL (12%) and AMC (18%) [28]. It is noteworthy a higher frequency of poultry isolates resistant to CIP (30.0%) compared with those from the other enterprise types.…”
Section: Resultssupporting
confidence: 92%
“…The AB resistance patterns per enterprise type revealed that the isolates from poultry farms had the highest resistance rates to TET, SXT, CHL and AMC (Figure 2). These results are in agreement with reports from: (i) Ghana, with high resistance frequencies to TET (88.9%), sulphonamide (75.0%), ampicillin (69.4%) and trimethoprim (66.7%) [25]; (ii) Madagascar broil farms with 97.6% to TET [26]; (iii) Chinese carcasses with ampicillin (98.9%), CHL (92.2%), TET (78.9%) [27]; and (iv) Portuguese healthy chickens with TET (70%), ampicillin (63%) and CIP (49%), however, with lower frequencies for SXT (33%), CHL (12%) and AMC (18%) [28]. It is noteworthy a higher frequency of poultry isolates resistant to CIP (30.0%) compared with those from the other enterprise types.…”
Section: Resultssupporting
confidence: 92%
“…Although, bla CTX−M has been reported as the most prevalent ESBL gene type in swine farms, and bla CTX−M1 and bla CTX−M9 are common in Thailand, the high occurrence of bla OXA−1 and bla VEB have not been reported from Thai agriculture farms (Hawkey, 2008;Suwantarat and Carroll, 2016;Lugsomya et al, 2018a). Detection of bla VEB was first reported from Vietnamese patients and low prevalence or rare detection in human clinical isolates was published in many country (Poirel et al, 1999;Doi et al, 2017;Gay et al, 2018). Interestingly, in our study bla VEB was enriched after weaning to 6 months of age, whereas bla CTX−M1 and bla CTX−M9 were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Although some potential risk factors, including management practices, had a tendency to be associated with the presence of 3GC-resistant isolates on farms, no risk factors for presence of 3GC-nonsusceptible isolates on farms were statistically significant in the multivariate model. Studies in Vietnam [ 64 ] and in countries of the South Western Indian Ocean [ 65 ] reported that management factors such as visitors allowed on farms and environmental mismanagement were associated with presence of ESBL/AmpC-producer E . coli on farms.…”
Section: Discussionmentioning
confidence: 99%